Long-term care insurance and labor-force participation of adult children: an analysis of substitution and anticipation effects - Yi, Yang; Gu, Jinghong; Xu, Qinglin; Gu, Hai (Frontiers in Public Health, 2025)
BackgroundMany informal caregivers at working age and face the dual burden of providing care and working. This study examines how China’s long-term care insurance (LTCI) pilot programs affect the labor-force participation of adult children who may provide informal care to parents.MethodsWe analyze four waves (2011, 2013, 2015, and 2018) of micro panel data from the China Health and Retirement Longitudinal Study and exploit the staggered rollout of LTCI pilots across cities from 2012 to 2017. A difference-in-differences design estimates the causal impact of LTCI implementation on labor-force participation of adult children, with robustness checks and subgroup analyses by gender, age, cohabitation status, and skill level.ResultsImplementation of LTCI significantly increases the likelihood of adult children remaining in the labor force. Mechanism analysis indicates this effect is driven by both reduced caregiving time (substitution effect) and improved expectations of future support (anticipation effect). The positive impact is particularly strong among men, individuals under 45 years old, cohabitation without parents, and lower-skilled workers.ConclusionExpanding LTCI can effectively alleviate the caregiving-employment conflict and enhance labor participation of adult children. To maximize workforce and social welfare benefits, policymakers should expand LTCI coverage, strengthen community care services, and focus support on high-burden caregiver groups.